Improving English Vocabulary for Elementary School Students using Total Physical Response (TPR) Method - Della Hegian Salsabila (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the increase in English Vocabulary ofElementary School Students Using the Total Physical Response (TPR) Method. In thisstudy, researchers using a quantitative approach with a quasi-experimental design fordoing a way to compare groups. There are three techniques in data collection includes:observation, pre-test and posttest. After collecting data, researchers analyze, describe andfinally conclude. Data will be analyzed using statistical analysis as follows with calculatethe mean score of the pre-test and post-test to find out whether there is a significantdifference in control and experimental groups. From this statement, it can be concludedthat the TPar method will affect student learning outcomes. Therefore, it is time forteachers, schools, and related parties to use the TPR method to improve the quality oflearning.